Challenges facing contemporary preimplantation genetic screening. Issue 3 (June 2016) - Juneau, Caroline; Franasiak, Jason; Treff, Nathan
Abstract : Purpose of review: Aneuploidy is a leading cause of pregnancy failure. Although initial attempts to perform preimplantation genetic screening did not improve outcomes, validated techniques were developed to safely and effectively increase pregnancy rates. Still, many embryos designated as euploid do not implant. Current approaches are being refined to provide additional biologic insight into why this is the case. At present, the diagnosis and clinical relevance of segmental aneuploidy and mosaicism are amongst the more heavily investigated. Recent findings: Class I data have proven the safety of trophectoderm biopsy and validation studies have shown single nucleotide polymorphism array and quantitative PCR can accurately detect whole chromosome aneuploidy. Similar studies to validate next generation sequencing are underway. Although randomized control trials have demonstrated the clinical utility of preimplantation genetic screening, recent data on the impact of mosaicism and segmental aneuploidy require clarification. Summary: Several well powered randomized control trials have shown preimplantation genetic screening improves implantation rate. Plausible explanations for euploid failures include undetected mosaicism and segmental aneuploidy. However, the true incidence and dispersion of mosaicism within the embryo is unknown. Likewise, the resolution of detection and clinical significance of segmental aneuploidy is unclear. Further research to validate proposed detection algorithms and class I data to determine if detection impacts outcomes is needed.